Dreaming-machine - Marek Wojtaszek (Angles)
The intensified sensory contact with digital media and their capacity to pre-cognitively extract sensible data and industrially reengineer experience make our existence increasingly feel like a dream. Through an examination of the aesthetic and ontological dimensions of dreams, this article argues for a reading of digital cultural production in terms of diurnal insomnia. What can a dreaming body do? Addressing that question, this essay will recast its insomniac capacities in non-representational terms. Drawing on Gilles Deleuze’s philosophical framework, the essay disentangles the traditional Western conception of dreams and develops an alternative proposition of a dreaming-machine. In doing so, the essay will make references to the film Inception (dir. Christopher Nolan, 2010), which is read as an aesthetically adequate rendition of the insomniac revolution in dreaming. Probing the vigilancy potential of insomnia for the political economy of contemporary digital culture, the essay postulates an aesthetics of exhaustion. Far from an algorithmic lullaby, digital culture is recast as an aesthetic exercise in insomniac exhaustion that allows us to experiment with alternative manners of dreaming (of) ourselves, our worlds and lives beyond digital/digitized consciousness.